Strengthening Food Security of Jember District Throug Commodity-Added Value Analysis Soybean in Agroindustry “Saudara Jaya” - Rachmat Udhi Prabowo; Sinta Tri Wahyuni (Jurnal Sinar Manajemen, 2025)
One of the development successes is in the agricultural sector related to food commodities. Food crops are one of the farming subsectors that have an important role in the Indonesian economy, such as providing added value for commodities that get treatment (agro-industry). An example of added value is making agricultural products as new products that are long-lived and ready for consumption. The added value generated can increase revenue. One of the farming subsectors that gets a lot of treatment (processing) is food commodities such as soybeans. Soybeans can be consumed directly or in processed form. Soybeans in processed form can be used as, tempeh, soy sauce, milk, sauce, and so on. is a snack made from soybeans and consumed as a companion to rice. Gebang Village is one of the villages in Patrang District, Jember Regency which has many agro-industries, one of which is "Saudara Jaya”. This study aims is to determine the added value of soybean processing in the "Saudara Jaya” agroindustry. The research methods used are descriptive and analytical. The data collection method uses primary and secondary data. Data analysis tools use value-added analysis using biological methods. The results showed that: The added value of "Saudara Jaya" agroindustry provides a positive value of Rp.7,970/kg, a value-added ratio of 32%, and a profit of Rp. 6,620/kg with a profit rate of 27% for large . Meanwhile, small-sized has a value-added result of Rp. 20,792/kg with a value added ratio of 60%, a profit of Rp. 20,214/kg with a profit rate of 59%.